Emotiveness and Persuasiveness: The Dialectic of Expressiveness in Communicative Processes (Texas Journal of Multidisciplinary Studies, 2024)
The work analyzes the influence of emotional expressiveness on the effectiveness of text communication. Emotivity, recognized by scientists as important for achieving communicative goals, manifests itself through expressiveness and "emotives" that influence the beliefs and perceptions of the audience. Emotive elements in the text enhance its persuasiveness, creating an emotional impact that can be diverse and multifaceted. The study emphasizes that a balanced combination of facts and emotionality in the text most effectively affects the reader, reflecting emotionality at the linguistic level and enhancing the expressiveness of the message.